Sex-Related Differences in Outcomes for Oropharyngeal Squamous Cell Carcinoma by HPV Status. (2nd May 2022) - Kao, Derek D.; Ferrandino, Rocco M.; Marshall, Deborah C.; Mutetwa, Tinaye; Miles, Brett; Bauml, Joshua M.; Sigel, Keith M.
Abstract : Background . Overall survival for HPV-associated oropharyngeal squamous cell carcinoma (OPSCC) has differed by sex, but little is known regarding cancer-specific outcomes. We assessed the independent association of sex with cancer-specific survival in patients with HPV-associated oropharyngeal squamous cell carcinoma (OPSCC). Methods . We identified 14, 183 patients from the Surveillance, Epidemiology, and End Results (SEER) program with OPSCC and tumor HPV status. We used Kaplan–Meier methods to compare overall survival (OS) and OPSCC-specific survival (HNCSS) by patient sex and by tumor HPV status. We then separately fit multivariable survival and competing risk models evaluating the association of sex on these outcomes by tumor HPV status and stratified by the use of guideline-concordant OPSCC treatment. Results . A total of 10, 210 persons with HPV-positive tumors (72.0%) and 3, 973 with HPV-negative tumors (28.0%) were identified. A larger proportion of women had HPV-negative tumors (24.0%) versus HPV-positive tumors (13.2%; p < 0.001 ). Women with HPV-positive tumors were less likely to receive guideline-concordant treatment compared to men. In unadjusted survival analyses, women did not differ in OS or HNCSS compared to men for HPV-positive tumors but had worse OS and HNCSS for HPV-negative tumors. After adjustment, men and women with HPV-positive OPSCC did not differ in OS or HNCSS. However, women with HPV-negative tumors faced worse overall survival (hazard ratio (HR) 1.15, 95% CI 1.02–1.29) that persisted even after stratifying for stage-appropriate treatment (HR 1.28, 95% CI 1.11–1.47). Conclusions . Women with HPV-positive OPSCC had similar survival outcomes compared to men, but those with HPV-negative tumors have worse overall and cancer-specific survival.